2014
DOI: 10.1371/journal.pone.0102421
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Adherence to and Compliance with the Portuguese Smoke-Free Law in the Leisure-Hospitality Sector

Abstract: BackgroundIn 2008, the Portuguese smoke-free law came into effect including partial bans in the leisure-hospitality (LH) sector. The objective of the study is to assess the prevalence of smoking control policies (total ban, smoking permission and designated smoking areas) adopted by the LH sector in Portugal. The levels of noncompliance with each policy are investigated as well as the main factors associated with smoking permission and noncompliance with the law.MethodsCross-sectional study conducted between J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 24 publications
(29 reference statements)
2
19
0
Order By: Relevance
“…In those venues, PM 2.5 levels were significantly greater than in non-smoking venues. As has been observed in Indonesia [20,21] and internationally [22,23,24], we found that non-enforcement of smoke-free laws fails to provide needed protection from SHS exposure for nonsmokers, including children. The PM 2.5 levels observed in this study were lower than those found in a 2009 convenience sample of 17 restaurants in Jakarta (~110 µg/m 3 ) [21] and in many similar venues sampled globally [16,25,26].…”
Section: Discussionsupporting
confidence: 63%
“…In those venues, PM 2.5 levels were significantly greater than in non-smoking venues. As has been observed in Indonesia [20,21] and internationally [22,23,24], we found that non-enforcement of smoke-free laws fails to provide needed protection from SHS exposure for nonsmokers, including children. The PM 2.5 levels observed in this study were lower than those found in a 2009 convenience sample of 17 restaurants in Jakarta (~110 µg/m 3 ) [21] and in many similar venues sampled globally [16,25,26].…”
Section: Discussionsupporting
confidence: 63%
“…The success of the legislation is contingent on the level of compliance. Currently, studies in the literature have compared levels of support13 and levels of compliance between partial and comprehensive bans,14 15 as well as assessed compliance with specifications of the law such as no active smoking or adopting ‘no smoking’ signs 16–18. Few studies,19–22 however, have looked further to assess specific factors or characteristics that shape compliance with the law, particularly within the hospitality sector.…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare professionals should be active in smoking prevention, as part of their daily practice [2][3][4][5][6][7]. Previous studies demonstrated that the attitude of healthcare professionals towards smoking is crucial for any long-term prevention and smoking cessation program [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In 2010, tobacco was responsible for 11800 deaths in our country. In 2012, more than a quarter of the population of 15 to 64 years was a tobacco consumer [4][5][6][7][8][9][10][11][12]. The majority of Portuguese started smoking consumption between 12 and 20 years of age, largely due to the influence of friends or curiosity and willingness to experiment.that it is imperative to invest in prevention and control of this important national public health problem [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation